P‐52: A Novel Six‐Mask Low‐Temperature Polycrystalline Silicon Architecture for TFT‐LCD Application. Issue 1 (25th September 2020) - Luo, Chengzhi; He, Peng; Xu, Yong; Song, Dewei; Liu, Guanghui; COOPER,; Tang, Fuxiong; Ai, Fei
Abstract : A novel six‐mask LTPS TFT architecture is fabricated and used in TFT‐LCD. The light shielding layer and organic layer are removed. Furthermore, the pixel indium tin oxide and source drain patterns are developed in one halftone mask. To solve the issue of high photo leakage current, we have investigated the generation mechanism of Iphoto and established guidelines for reducing it. The optical and electrical characteristics of the six‐mask TFT‐LCD are comparable to those of conventional TFT‐LCD.